Bubble production by capillary‐gravity waves - Kolaini, A; Crum, L; Roy, R (Acoustical Society of America, 1994)
In the absence of whitecapping, other physical mechanisms may contribute to the generation of high‐frequency ambient noise. It has been suggested [Longuet‐Higgins, in NATO Advanced Research Workshop on Sound Generation Mechanisms at the Open Surface (NATO, Geneva, 1987)] that capillary waves, with surface profiles that are peaked downward in the troughs and are relatively flat at the crests, can inject acoustically active bubbles into the ocean, and thus contribute to the ambient noise background. It has been demonstrated in the laboratory that bubble injection can be generated at the trough of capillary‐gravity, short‐fetched waves by blowing air over water contained in a long, narrow tank. Simultaneous in situ acoustic and high‐speed video monitoring of the capillary‐gravity waves demonstrate that these waves can produce acoustically active bubbles. The generation of capillary waves depends principally upon the surface tension, which can be changed by adding surface‐active agents to the water. The bubble production rate per unit area of these capillary‐gravity waves was measured, as well as the dependence of this rate on wind speed, laboratory wind fetch, and surface tension. It was determined that an increase in water salinity and a reduction in surface tension increases the bubble production rate. The spectra of radiated frequencies ranges from 1 kHz to over 100 kHz with a broadband peak located around 4 kHz. The measured spectral densities were weakly related to wind speed. The wind‐speed threshold value for bubble production was determined to be approximately 8.6 m/s (14.6 m/s at 10‐m level) in fresh water and salt water, which decreased to 8.1 m/s (13.8 m/s at 10‐m level) with a surface tension of 40.5 dyn/cm.